Correlação entre estado de dispersão, propriedades eletrocinéticas e flotabilidade de hematita - Júnia Soares Alexandrino (2013)
Studies aiming to improve the beneficiation of iron ores are highly relevant. The grade of the valuable mineral in the ores being mined is steadily decreasing. The lower grade ores require finer grinding. Iron oxides and hydroxides acquire surface charge when dispersed in aqueous medium. The changes on the surface of oxides and the formation of an electrically interface between the particles and the aqueous medium are controlled by the pH and the ionic strength of the solution. These factors lead to the need of investigating the effect of dispersion on the stages of flotation, thickening, and filtration. This laboratory scale study aimed to contribute to the understanding of iron ores flotation, addressing the correlation among dispersion, zeta potential, and microflotation of hematite. The dispersion of mineral particles in the pulp is a key factor to the flotation selectivity of these ores. Initially dispersion experiments were performed on a compact hematite sample presenting Fe, SiO2, Al2O3, and PPC contents of 69.45%, 0.29%, 0.05%, and 0.05%, respectively. Fourteen organic and inorganic dispersants were evaluated in the dispersion experiments. In the absence of reagents the hematite dispersion degree was very low in the pH range between 6.5 and 7.5. The isoelectric point was determined in this pH range (pH = 6.8), in which a trend to aggregation was observed. In the dispersion experiments the dispersant dosage was varied and those causing relevant changes in the dispersion degree were selected to be used in the microflotation experiments. Most of the reagents rendered the hematite zeta potential less negative then that measured in the absence of reagents. Among the reagents used in microflotation, the lowest dispersion degree was achieved in the presence of the collector ethermonoamine. Sodium silicates increased the hematite floatability in the presence of monoamine. Sodium silicate C112, presenting the lowest Na2O:SiO2 ratio, provide the highest increase in hematite floatability in the presence of both collectors used.